MALIGNANT STRUMA OVARII: A CLINICO-PATHOLOGICAL STUDY. (February 2015) - Tan, Adeline; Cohen, Paul
Abstract : Aims: To study CK-19, HMBE-1 and galectin-3 staining in malignant struma ovarii and correlate the findings with tumour morphology, clinical outcome and the presence of BRAF mutations and RET proto-oncogene rearrangements. Methods: This is a clinico-pathological study of all MSOs accessioned in the histopathology departments in Western Australia from 1989 to the present. Three cases have been identified and data are extracted from the patient's medical record. Clinical outcomes will be recorded with a specific focus on: 1. Patient demographics including age at diagnosis. 2. Stage of disease at diagnosis. 3. Extent of surgery performed. 4. Adjuvant treatment such as thyroxine or radioiodine ablation. 5. Presence of co-existent thyroid malignancy. 6. Disease recurrence. 7. Cancer-specific survival and overall survival. Immunophenotyping of fixed formalin paraffin embedded slides: staining with antibodies for CK19, HMBE-1 and galectin-3 is assessed semi-quantitatively according to the extent and intensity of staining. Tumours are assessed as score − (no staining), score + (weak or moderate staining in < 50% of cells), or score +  + (moderate or strong staining in > 50% cells). The presence of BRAF mutations and RET proto-oncogene rearrangements will be determined by RT-PCR following DNA extraction from the FFPE slides. Results and discussion: Results are still pending at time of this abstract. Inter-group comparisons will be made by Fisher's exact test. P  < 0.05 will be considered statistically significant. Due to its rarity, our knowledge of the clinical behaviour of MSO is based on case reports and small case series. Rates of coexisting primary thyroid carcinoma are not known. Recurrence rates after initial surgical treatment vary, but may be as high as 35% with a median time to recurrence of 4 years. Few studies have assessed the correlation of certain pathological parameters (e.g., tumour size, histological pattern, immunophenotype, BRAF mutation status, RET gene rearrangement) with increased risk of recurrence, and it is less clear whether these risk factors are significant in patients presenting with early stage disease.